PSYCHOPATHIC BEHAVIOUR OF THE MAIN CHARACTERS IN TED TALLY’S MOVIE “THE SILENCE OF THE LAMBS” - Syam, Adeliah Nurmuthmainnah; Nur, Sahril; Iskandar, Iskandar (Journal of English Literature and Linguistic Studies, 2022)
In this study, researcher analyzed the symptoms that arise from psychopathic disorder. The researcher analyzed 2 problems, they are: (1) What are the symptoms of the main characters potrayed in the movie "The Silence of the Lambs"? (2) What are the factors that cause the main characters of “The Silence of the Lambs” become a psychopath? The movie "The Silence of the Lambs" is a 1991 film directed by Jonathan Demme and adaptation of the novel by Thomas Harris. The method used in this study is qualitative descriptive method and a psychological approach. Based on the findings, there are 8 psychopathic symptoms that appear in this movie. Hannibal Lecter's character has 6 psychopathic symptoms, namely Glib and superficial, Lack of remorse or guilt, Lack of empathy, Deceitful and manipulative, Impulsive, and Poor behavior controls. Meanwhile, Buffalo Bill's character has 6 psychopathic symptoms, namely Egocentric and grandiose, Lack of remorse or guilt, Lack of empathy, Deceitful and manipulative, Poor behavior controls, and Early behavior problems. The factor that causes Hannibal Lecter's character to become a psychopath is Trauma. Meanwhile, Buffalo Bill's character being a psychopath is Ultimate Causa